Microsoft 70-415 : implementing a desktop infrastructure - Sutton, Darin; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"The new and exciting Advanced Server 2012 course provides full coverage of the knowledge and skills required to plan and implement the more advanced features available in Server 2012. This new course provides you the needed training for the complete Implementing a Desktop Infrastructure."--Resource description page.
Presenter, Darin Sutton.
Title and publication information from resource description page (Safari, viewed April 20, 2017).
Presenter's name from title screen.
Keywords: Microsoft Windows server -- Certification -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books